Rural Finance Policies 1 - The demand for financial services by the rural poor - Zeller, Manfred; Sharma, Manohar (International Food Policy Research Institute, 2000)
This policy brief summarizes lessons learned from IFPRI's multicountry program on rural finance and household food security with regard to the poors’ demand for financial services. The lessons are derived from detailed household surveys conducted in nine countries of Asia and Africa: Bangladesh, Cameroon, China, Egypt, Ghana, Madagascar, Malawi, Nepal, and Pakistan.